Rising Income Inequality and Living Standards in OECD Countries: How Does the Middle Fare? - Thewissen, Stefan; Kenworthy, Lane; Nolan, Brian; Roser, Max; Smeeding, Tim (Journal of Income Distribution®, 2018)
Income inequality has increased in a number of the rich democratic nations over the past generation. We examine whether this has reduced income growth for middleincome households. Using LIS, OECD and WID data, we show how median household incomes and income inequality have evolved between 1980 and 2013, and we analyse whether these trends are related. Growth in median incomes is negatively associated with changes in the Gini but not with changes in top income shares. Economic growth is strongly associated with growth in median incomes, although it does not seem to fully transmit.